Structural and morphological studies on alkaline pre-treatment of oil palm empty fruit bunch (OPEFB) fiber for composite production - Noraishah, Latip; Azizul Helmi, Sofian; M. F., Ali; S. N., Ismail; D. M. N. D., Idris (Elsevier Ltd, 2019)
Empty fruit bunch from the palm oil industry can be classified as a popular source among various waste streams in Malaysia as one of recyclable raw material that offered broad useful applications especially in bio-composite production. This is due to its abundantly generation, inexpensive and high mechanical properties. However, one of the major weakness of oil palm empty fruit bunch (OPEFB) is their hydrophilic characteristic that will cause the weak binding between the interaction of fiber and polymer matrix during the composite production. Thus, the pretreatment needs to be done in order to improve their compatibility. In this work, the effect of alkali pretreatment by using different alkaline solutions of 15% (w/v) concentration at 130°C and for 40 minutes with fiber to solution ratio at 1:20 have been investigated. Their physicochemical and structural behavior were studied in details by several analysis which are Fourier Transform Infrared (FTIR), Scanning Electron Microscopy (SEM) and X-ray Diffraction (XRD). The experimental result showed that FTIR analysis expressed quite same spectra for NaOH and KOH treated OPEFB fiber in term of the decreasing in ester linkage stretching, aromatic groups and also lignin. SEM observation also contributed to highlight these changes by exposing their structure and morphology of treated fiber. Meanwhile XRD analysis clearly observed that the highest crystallinity index was 60.8% by KOH solution just slightly different from the NaOH solution by 0.5% compared to Al(OH)3 solution by 22.9%. From this finding, the modification of OPEFB fiber through alkaline pretreatment by three different alkali solution gave some changes to the nature of OPEFB fiber and can be seen clearly that both NaOH and KOH gave better perspective in term of the hydrophilicity reduction and surface effectiveness as well as cellulose structure improvement. Hence these transformations literally affected and contributed to the improvement in bonding strength with thermal stability that can be applied generally for advanced polymer composite production.